Gear Drive Mechanism for Continuous Variable Valve Timing of IC Engines - Nakkeeran, S. (International Journal of Psychosocial Rehabilitation, 2019)
Continuous variable valve actuating (CVVA) technology provides high potential in achieving high performance, low fuel consumption, and pollutant reduction. To get full benefits from CVVT, various types of mechanisms have been proposed and designed. Some of these mechanisms are in production and have shown significant benefits in improving engine performance. In this investigation, a newly designed gear drive mechanism that controls the intake valve opening (IVO) and closing (IVC) angles is studied. The control scheme is based on maximizing the engine brake power (P) and specific fuel consumption (BSFC) at any engine speed by continuously varying the phase between the cam shaft angle and the crank shaft angle. A single-cylinder engine is simulated by the “LOTUS” software to find out the optimum phase angle for maximum power and minimum fuel consumption at a given engine speed. The mechanism is a planetary gear drive designed for precise and continuous control. This mechanism has a simple design and operation conditions that can change the phase angle without limitation.